ETNOMATEMATIKA PADA PERMAINAN CANANG KEPULAUAN RIAU - Puji Astuti; Febrian Febrian; Afdillah Afdillah; Herda Nurmelia; Khofifah Intan Nur Fitriani; Melisawati Melisawati; Putri Sekar Sari; Tasya Ambarini (Universitas Sriwijaya, 2023)
Efforts are still needed to increase students awareness of the existence of mathematics in everyday life so that ethnomathematics studies need to be encouraged. This study aims to describe and examine more deeply the mathematical activities and mathematical concepts contained in the traditional canang game played in West Bunguran Barat, Pulau Tujuh , Riau Archipelago Province, as well as to remind the community of this traditional canang game. This game has spread to various areas in the Riau Islands, one of which is the area in Sungai Lekop Village. The subjects of this study were children in the Sungai Lekop Village, Riau Archipelago Province. This study uses a type of qualitative research with an ethnographic approach. The focus of this research is the basic concept of the traditional canang game and how to play it. In this study the researcher acts as the main instrument. Data collection techniques used are direct observation, interviews, and documentation. This study also used Spradley data analysis which consisted of several stages, namely domain analysis, taxonomic analysis, component analysis, and cultural theme analysis. The results showed that there were mathematical activities such as counting, measuring, playing, explaining/classifying, and comparing. In addition, there are mathematical concepts in the form of integer operations, comparisons, displacements and distances.